Proceedings of the Conference on Recent Advances in Rock Engineering (RARE 2016) 2016
DOI: 10.2991/rare-16.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Strata control monitoring in a contiguous seam depillaring working

Abstract: -Most of the underground coal mines in the Indian Geo-mining conditions are developed and depillared by Bord and Pillar method. Caving behaviour and strata control are the major concerns to be considered while extraction of coal seams in such workings. This paper describes the results of a scientific strata control monitoring study during depillaring in a contiguous seam working. It includes instrumentation for determining the induced stresses in the pillars and roof-floor convergence in the galleries and junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In increasing the number of splitting of macronutrients, N and K might have facilitated their even availability in soil throughout the development of cane, which ultimately led to a quicker rate of crop growth (Junejo et al, 2010). These results also confirm the findings recorded by Sandeep et al (2013). The highest N, P, and K uptakes in sugarcane crops at harvest in plant and ratoon crops were found in 7 split-application of N and K. Many previous studies also reported similar results.…”
Section: Discussionsupporting
confidence: 90%
“…In increasing the number of splitting of macronutrients, N and K might have facilitated their even availability in soil throughout the development of cane, which ultimately led to a quicker rate of crop growth (Junejo et al, 2010). These results also confirm the findings recorded by Sandeep et al (2013). The highest N, P, and K uptakes in sugarcane crops at harvest in plant and ratoon crops were found in 7 split-application of N and K. Many previous studies also reported similar results.…”
Section: Discussionsupporting
confidence: 90%
“…Outside cavity conditions, it is reported that the solvent reorganization entropy affects the dispersion interactions in the studied molecule whereas the dispersion enthalpy remains constant upon changing the solvent. The modification of solvent properties under VSC (14,22) might therefore derive from changes to solvation entropy due to N-1 dark states which appear when N molecules are coupled to a given optical mode (45), as in these experiments. The details of the various contributions are beyond this study and would benefit from further theoretical analysis.…”
Section: Introductionmentioning
confidence: 83%
“…Under the right conditions, this interaction gives rise to two hybrid light-matter vibropolaritonic states (VP+ and VP-) along with N-1 dark collective states (DS) resulting from the coupling of N molecules with the optical mode. The formation of these hybrid states, which occurs in the dark, has been shown to alter reaction rates (3)(4)(5)(6)(7)(8)(9)(10), chemical selectivity (11)(12)(13), electrochemical modulation (14), charge transfer equilibria (15) and many other properties such as ionic conductivity (16,17), electrical conductivity (18), solvent polarity (19), crystallization (20) or self-assembly (21,22). Despite the numerous experimental studies of chemistry and properties under VSC and extensive theoretical studies (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), a detailed understanding of the underlying processes is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two major types of phages, lytic and lysogenic. Only the lytic phages (also known as virulent phages) are a good choice for developing therapeutic phage preparations (24,25). The bactericidal ability of phages has been used to treat human infections for years as a complement or alternative to antibiotic therapy (26,27,28).…”
Section: Mrsa Stands For Methicillin-resistantmentioning
confidence: 99%